MR Imaging of Hyperacute Subarachnoid and Intraventricular Hemorrhage at 3T: A Preliminary Report of Gradient Echo T2*-Weighted Sequences - Sohn, Chul-Ho; Baik, Seung-Kug; Lee, Hee-Jung; Lee, Sung-Moon; Kim, Il-Man; Yim, Man-Bin; Hwang, Jae-Suk; Lauzon, M. Louis; Sevick, Robert J. (American Journal of Neuroradiology, 2005)
Summary: We describe MR imaging findings applying gradient echo (GRE) T2*-weighted and fluid-attenuated inversion recovery (FLAIR) MR images at 3T to three patients with hyperacute subarachnoid and intraventricular hemorrhage from ruptured aneurysms. Hyperacute subarachnoid and intraventricular hemorrhages (SAH and IVH) were more clearly visualized as an area of decreased signal intensity on GRE T2*-weighted sequences than on FLAIR sequences in all three patients. These preliminary results suggest that acute SAH and IVH with GRE T2*-weighted imaging can be reliably diagnosed at 3T.